2016
DOI: 10.1016/j.atherosclerosis.2016.03.040
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ in bone marrow is essential for diet induced inflammation, cholesterol balance, and atherosclerosis

Abstract: Background and Objective Atherosclerosis is both a chronic inflammatory disease and a lipid metabolism disorder. C/EBPβ is well documented for its role in the development of hematopoietic cells and integration of lipid metabolism. However, C/EBPβ's role in atherosclerotic progression has not been examined. We assessed the impact of hematopoietic CEBPβ deletion in ApoE−/− mice on hyperlipidemia, inflammatory responses and lesion formation in the aorta. Methods and Results ApoE−/− mice were reconstituted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Apoe −/− mice reconstituted with C/EBP β‐deficient bone marrow cells exhibited lower levels of serum LDL cholesterol and reduced atherosclerotic lesions compared with Apoe −/− mice reconstituted with wild‐type bone marrow cells (Rahman et al . ). They also showed that C/EBP β deficiency in Raw264.7 macrophage cells prevented oxidized LDL‐mediated foam cell formation and inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 97%
“…Apoe −/− mice reconstituted with C/EBP β‐deficient bone marrow cells exhibited lower levels of serum LDL cholesterol and reduced atherosclerotic lesions compared with Apoe −/− mice reconstituted with wild‐type bone marrow cells (Rahman et al . ). They also showed that C/EBP β deficiency in Raw264.7 macrophage cells prevented oxidized LDL‐mediated foam cell formation and inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, C/EBPβ was first found as a key regulator of IL-6 production [20]. Other studies have indicated that C/EBPβ may play important roles in the regulation of other inflammatory factors, such as IL-1β, MCP-1 and TNF-α [19]. However, the mechanisms by which C/EBPβ regulates inflammatory factors in macrophages, such as IL-1β production, in macrophages are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPβ is a basic Leucine Zipper (bZIP) transcription factor which binds to certain DNA regulatory regions to regulate gene expression [18]. Knockout of C/EBPβ gene in mice shows significant reduction of inflammatory cytokine levels and lesion areas in aortic sinuses compared with wildtype mice [19]. Generally, C/EBPβ was first found as a key regulator of IL-6 production [20].…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Rahman et al published in this issue of Atherosclerosis has identified a novel role for CCAAT/enhancer-binding protein b (C/EBPb) in atherosclerosis [5]. C/EBPb is a member of the basic leucine zipper family of transcription factors that is highly expressed in myelomonocytic cells and macrophages, and is increasingly recognised as an important regulator of monocyte/ macrophage activities [6e8].…”
mentioning
confidence: 99%
“…In light of the implications of C/EBPb for macrophage function and lipid metabolism, Rahman et al have investigated for the first time the role of haematopoietic-expressed C/EBPb in atherosclerosis [5]. This study reports that reconstitution of irradiated ApoE À/ À mice fed a high-fat, high-cholesterol diet for 11 weeks with bone marrow from C/EBPb À/À mice resulted in (i) a significant reduction in circulating levels of LDL cholesterol and pro-inflammatory cytokines (TNF, IL-1b, Il-6, MCP-1), (ii) a >50% decrease in hepatic lipid levels that correlated with a reduction in fatty acid synthetic enzymes and increase in cholesterol metabolic and efflux genes, and (iii) an approximately 2-fold reduction in atherosclerotic lesion size at the aortic sinus (examination of how C/EBPb deficiency impacts on atherosclerosis at the aortic arch or more distal sites was not reported).…”
mentioning
confidence: 99%